1980
DOI: 10.1107/s056774088000948x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the monopotassium salt of adenosine 5'-diphosphate dihydrate, KADP.2H2O

Abstract: Crystals of the title compound, K ÷.C~0 HI4-NsOioP 2. 2H20, were grown at pH 4 from a water/ ethanol mixture. They have space group P2~2~2 with a = 28.502 (5), b = 10.461 (2), c= 6.321 (2) A,Z= 4, D c = 1.76 Mg m -3. The structure was solved from 1726 three-dimensional X-ray diffraction data and refined to Rw = 9.3%. The ribose adopts the C(2')-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…An anti conformation is preferred and most frequently reported for nucleoside 5 0 -diphosphate structures, e.g. ADP (Adamiak & Saenger, 1980;Shakked et al, 1980) and UDP (Viswamitra et al, 1979), and also in 2 0 :3 0isopropylideneadenosine (Sprang et al, 1978) and other nucleotides where the pyrophosphate structural motif can be found, e.g. NAD + (Reddy et al, 1981;Guillot et al, 2000).…”
Section: Geometry and Conformation Of The Nucleotide Moiety In (I) Anmentioning
confidence: 96%
See 1 more Smart Citation
“…An anti conformation is preferred and most frequently reported for nucleoside 5 0 -diphosphate structures, e.g. ADP (Adamiak & Saenger, 1980;Shakked et al, 1980) and UDP (Viswamitra et al, 1979), and also in 2 0 :3 0isopropylideneadenosine (Sprang et al, 1978) and other nucleotides where the pyrophosphate structural motif can be found, e.g. NAD + (Reddy et al, 1981;Guillot et al, 2000).…”
Section: Geometry and Conformation Of The Nucleotide Moiety In (I) Anmentioning
confidence: 96%
“…not coordinated). The remaining three crystal structures are ADP potassium salt dihydrate [KADPHD01 (Adamiak & Saenger, 1980; H-atom positions not determined) and KADPHD02 (Swaminathan & Sundaralingam, 1980)], ADP rubidium salt monohydrate [RBADPM10 (Viswamitra et al, 1976); no H-atom positions] and ADP tris salt [tris is tris(hydroxymethyl)methylammonium] dihydrate [HMADPH (Shakked et al, 1980); no Hatom positions]. In KADPHD02, the positions of the H atoms seem to be incorrect; thus, an analysis of the hydrogen bonds in the K, Rb and tris salts of ADP is difficult.…”
Section: Comparison Of the Solid-state Conformation Of Ahdp With Adpmentioning
confidence: 99%
“…Oligonucleotides were synthesized using nucleoside phosphoramidite derivatives obtained from Milligen (New Bedford, MA) and an Applied Biosystems 381A DNA synthesizer. High-performance liquid chromatography (HPLC) was carried out on an ODS-Hypersil column (0.46 × 25 cm, Shandon Southern, England), using a Beckman HPLC system. Absorption spectra were recorded by a Perkin-Elmer Lambda 3B UV/vis spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Note: We thank one of the referees for drawing our attention to a recent preliminary communication on the same structure . We have also learned from Dr W. Saenger, after this paper was submitted for publication, that he too had submitted a paper on the same crystal structure (Adamiak & Saenger, 1980) (previous paper). The overall features of the structure are the same in the two determinations with the exception of some significant differences in the geometrical parameters.…”
Section: Comparison Of the Molecular Conformations Of Adp And A Tp Inmentioning
confidence: 95%